(3eaGJjM GdCUhds - (3GdWHGWHGFj GdcQHdGFj, GdeLGgO, eMeO Hf Ydj Hf eMeO Hf Ydj, J (B1242 (3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3heG CQSdfG ef QShd EdG HdSGf bheg(B...s
(3BNQgG (B:s
(3hceG dh fSN SfI ef Sff cfSN SJQ GdQCS hGdhbha Ydi Yjf GdCMcGe (B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI Qbe(B: 5173s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3CUhd Gdabgs